The effectiveness of different handstand placement techniques in handstand balance control and gender differences - Milosis; D.; Satras, T. (Science of Gymnastics Journal, 2023)
The purpose of the study was twofold: (a) to examine the impact of various finger placements and utilization on the quality, control, and overall efficiency of handstand performance, and (b) to investigate potential gender differences in relation to these factors. Thirty-one young competitive gymnasts (15 males; age: 12.60 ± 2.08, and 16 females; age: 13.31 ± 2.21) participated in this study. A portable posturographic digital platform was used to record hand area (cm²), maximal pressure (kPa), CoP (center of hand pressure) sway area (mm²), CoP linear distance displacement (mm) and CoP velocity. Derived data were analyzed in an integrated software module (Foot Checker, version 4.0). The intra-class correlation coefficient and the coefficient of variation supported the reliability of the measurements. One-way MANOVA showed better balance control for all gymnasts for the handstand with flat palms and joined and fully stretched fingers, followed by that of flat palms and wide open and fully stretched fingers, and wide flat palms and open and flexed fingers. Results from one-way MANOVA indicated no differences between males and females in age, training age, body mass, height, and body mass index. With control for the effects of age, training age, personal characteristics and hand area of support in place, females had better balance control compared to males based on differences in CoP sway area, CoP linear distance displacement, and CoP velocity. Despite the study's limitations, the findings contribute to the existing literature on balance control techniques in handstands in relation to gender differences. The study provides recommendations for more effective training for coaches and suggests avenues for future research.